Knowledge and Practice of Pharmacists toward Antimicrobial Stewardship in Pakistan - Inayat Ur Rehman; Malik Muhammad Asad; Allah Bukhsh; Zahid Ali; Humera Ata; Juman Abdulelah Dujaili; Ali Qais Blebil; Tahir Mehmood Khan (MDPI AG, 2018)
Background: The irrational use, “over the counter supply„, and unregulated supply chains of antimicrobials are contributing toward antimicrobial resistance. Antimicrobial stewardship programs regulate antimicrobials usage to prevent resistance and reduce health care burden. Objective: To assess the knowledge and practice of pharmacists’ working in various healthcare settings toward antimicrobial stewardship in Pakistan. Method: A cross-sectional study was conducted among pharmacists working in different sectors between March to June 2017. Results: A total of 181 pharmacists participated, of whom (n = 145, 80.1%) were males. The majority of participants were in the 20⁻30 age group (n = 147, 81.2%) and hold Doctor of Pharmacy degrees. More than 80% of pharmacists agreed that “antimicrobial stewardship is essential to improve patient care„; while (n = 159, 87.8%) pharmacists agreed that “pharmacist should be trained on the use of antimicrobial„. Close to 90% of pharmacists agreed that “adequate training should be provided to pharmacists on antimicrobial use„. Regarding the practice of antimicrobial stewardship, (n = 72, 39.8%) pharmacists often/always “make efforts to prevent or reduce the transmission of infections within the community„; (n = 58, 32%) pharmacists never “dispense antimicrobials without a prescription„; and (n = 60, 32%) pharmacist often/always “communicate with prescribers if unsure about the appropriateness of an antibiotic prescription„. Conclusions: Increased antimicrobial stewardship efforts can both optimize the treatment of infections and reduce adverse events associated with antibiotic use. Pharmacists in Pakistan have good knowledge and adopt positive practices toward antimicrobial stewardship. Pharmacist and other health care professionals should collaborate within multi-disciplinary teams to reduce the problem of antimicrobial resistance and improve the quality of life of patients.